Efficacy of Second-Line Antiretroviral Therapy Among People Living With HIV/AIDS in Asia: Results From the TREAT Asia HIV Observational Database. (1st February 2015) - Boettiger, David C.; Nguyen, Van K.; Durier, Nicolas; Bui, Huy V.; Heng Sim, Benedict L.; Azwa, Iskandar; Law, Matthew; Ruxrungtham, Kiat
Abstract : Background: Roughly 4% of the 1.25 million patients on antiretroviral therapy (ART) in Asia are using second-line therapy. To maximize patient benefit and regional resources, it is important to optimize the timing of second-line ART initiation and use the most effective compounds available. Methods: HIV-positive patients enrolled in the TREAT Asia HIV Observational Database who had used second-line ART for ≥6 months were included. ART use and rates and predictors of second-line treatment failure were evaluated. Results: There were 302 eligible patients. Most were male (76.5%) and exposed to HIV via heterosexual contact (71.5%). Median age at second-line initiation was 39.2 years, median CD4 cell count was 146 cells per cubic millimeter, and median HIV viral load was 16, 224 copies per milliliter. Patients started second-line ART before 2007 (n = 105), 2007–2010 (n = 147) and after 2010 (n = 50). Ritonavir-boosted lopinavir and atazanavir accounted for the majority of protease inhibitor use after 2006. Median follow-up time on second-line therapy was 2.3 years. The rates of treatment failure and mortality per 100 patient/years were 8.8 (95% confidence interval: 7.1 to 10.9) and 1.1 (95% confidence interval: 0.6 to 1.9), respectively. Older age, high baseline viral load, and use of a protease inhibitor other than lopinavir or atazanavir were associated with a significantly shorter time to second-line failure. Conclusions: Increased access to viral load monitoring to facilitate early detection of first-line ART failure and subsequent treatment switch is important for maximizing the durability of second-line therapy in Asia. Although second-line ART is highly effective in the region, the reported rate of failure emphasizes the need for third-line ART in a small portion of patients.